Pengaruh Lingkungan Kerja, Stress Kerja Dan Kompensasi Terhadap Kinerja Karyawan KBPR Arta Kencana Cabang Nganjuk - Merlina Aris Fitria Dewi; Indah Respati Kusumasari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Companies have the ability to assess the skills and responsibilities of employees through their performance results, which play a role in achieving company goals. Researchers conducted research to investigate the effect of work environment, work stress, and compensation on employee performance. The use of quantitative methods with data collection tools, namely questionnaires or questionnaires. The population and research sample included all employees at KBPR Arta Kencana Cabang Nganjuk . The results of the analysis of this study are that there is a simultaneous and significant influence between the work environment, work stress, and employee performance of KBPR Arta Kencana Cabang Nganjuk . In particular, there is a partial influence between the work environment on employee performance, while work stress does not have a significant partial influence on employee performance at the branch. In line with the work environment, compensation also has a partial and significant effect on employee performance. It is important for companies to pay attention to the work environment and provide appropriate compensation, as higher compensation levels correlate with better employee performance.